Clinical and microbiological characteristics of onychomycosis in a tertiary hospital: a cross-sectional study - Widaty, Sandra; Oktarina, Caroline; Marissa, Melani; Adawiyah, Robiatul; Rozaliyani, Anna; Kartika, Emiliana; Tugiran, Mulyati (Medical Journal of Indonesia, 2024)
BACKGROUND Onychomycosis is a common fungal nail infection with a low cure rate. While dermatophytes are the most common causal agent for onychomycosis, the incidence of Candida and nondermatophyte mold (NDM) onychomycosis is increasing. This study aimed to analyze the clinical and microbiological characteristics of patients with onychomycosis. METHODS Patients who visited the Department of Dermatology and Venereology, Cipto Mangunkusumo Hospital, and were diagnosed with onychomycosis from 2017 to 2022 were included. Diagnosis was established through clinical examination, supported by the result of direct microscopic examination with potassium hydroxide. RESULTS Of 171 patients, 93.6% had onychodystrophy, 65.5% were females, and 62.0% were aged 19–59 years. Most patients had onychodystrophy in more than three nails, affecting fingernails (31.6%) and toenails (34.5%). Interestingly, 84.8% of patients had no history of nail diseases. The median onset of disease was 24.0 (1–1,040) weeks, while the median onychomycosis severity index was 10.0 (2–40). Most cases were caused by Candida albicans (48.3%). Fusarium was the only NDM documented (2.3%). Some patients were resistant to itraconazole (11.4%) and miconazole (4.5%). Overall, 49.1% of the patients were declared not cured. CONCLUSIONS Candida was the predominant cause of onychomycosis, and onychodystrophy was the dominant feature. Current treatment regimens with systemic or topical antifungal agents did not yield satisfactory results, with more than half of the patients deemed not cured.